Paraglacial Modifications of Glacial Sediments Over Millennial to Decadal Time-Scales in the High Arctic (Billefjorden, Central Spitsbergen, Svalbard) - Rachlewicz, Grzegorz (Quaestiones Geographicae, 2010)
The paper discuss the morphologic expression and sedimentological record left after the operation of glacial episodes in the area of Billefjorden, central Spitsbergen, in the period of Late Pleistocene ice-sheet development and in the last advance of glaciers in the Little Ice Age (LIA) around the beginning of the 20th century. No evidence is found for other Holocene glacier advances. Paraglacial activity during several millennia erased the surface expression of Pleistocene glacial deposits, leaving a widespread set of reworked material that adopts features of slope, fluvial, aeolian or littoral environments. Glacial features generated during the past century, and still forming in front of retreating glaciers, undergo intense paraglacial modifications limited to the maximum depth of permafrost thaw during the summer. They deliver vast amounts of erosion-susceptible material from mass movements on buried ice fragments, through the glaciofluvial system to aeolian and littoral activity.